Russia and India in the Evolving World Order. Introduction to the special issue - Nandan Unnikrishnan; Nivedita Kapoor (Vestnik MGIMO-Universiteta)
The introductory article delves into the evolving dynamics of the India-Russia relationship in the post-Soviet era, characterized by carefully forged cooperation, managed differences, and adaptation to the ever-changing international landscape. The authors emphasize that amidst the current state of global disorder, India and Russia can mutually assist each other within certain constraints. The article highlights how bilateral ties enable Moscow and New Delhi to pursue their national interests, with a commitment to safeguarding their respective sovereignty. The authors propose a nuanced understanding of the relationship, wherein India and Russia continue to engage in ways that uphold their own interests and prevent any infringement upon each other. The article sets the stage for further exploration of the numerous facets of the IndiaRussia relationship, examining areas such as strategic cooperation, economic ties, multilateral engagement, and addressing global challenges like climate change. Ultimately, it aims to provide insights into the complex and evolving nature of this bilateral partnership.